‘Finally shall come the poet, worthy that name’: exploring the role of a cathedral poet-in-residence - Harper, Sally (Journal of beliefs and values, 2025)
Cathedrals have been hosting poets- and writers-in-residence since 1998, when the first ‘cathedral poet’ came to Worcester under the Poetry Places scheme. Such residencies are steadily increasing, although they reveal mixed priorities and portfolios. Some poets come as unpaid volunteers to reflect primarily on the varied aspects of cathedral life and to offer creative workshops; others may receive external funding to work on a cathedral outreach programme, sometimes in partnership with another institution. The outcome of a residency may be equally varied, ranging from a traditional volume of ‘cathedral poems’ to spontaneous ‘spoken word’ poetry, emphasising performance and community interaction. The very distinctiveness of English cathedrals suggests that there is no obvious blueprint for a successful residency, although the capacity of poetry to help us ‘see differently’ suggests increasingly creative ways in which a poet may transform our encounter with a cathedral and all that it stands for.